Enhancement of neurite outgrowth using nano-structured scaffolds coupled with laminin - Koh, H.S.; Yong, Thomas; Chan, C.K.; Ramakrishna, S. (Biomaterials, 2008)
Cell interactions with scaffolds are important for cell and tissue development in the process of repairing and regeneration of damaged tissue. Scaffolds that mimic extracellular matrix (ECM) surface topography, mechanical stiffness, and chemical composition will be advantageous to promote enhanced cell interactions. Electrospinning can easily produce nano-structured synthetic polymer mats with architecture that structurally resembles the ECM of tissue. Although electrospinning can produce sub-micron fibrous scaffolds, modification of electrospun scaffolds with bioactive molecules is beneficial as this can create an environment that consists of biochemical cues to further promote cell adhesion, proliferation and differentiation. Incorporation of laminin, a neurite promoting ECM protein, onto the nanofibers is an alternative to further mimic the biochemical properties of the nervous tissue to create a biomimetic scaffold. In this study, we investigated the feasibility to functionalize scaffolds by coupling laminin onto poly( l-lactic acid) (PLLA) nanofibers. Laminin was successfully added to nanofibers using covalent binding, physical adsorption or blended electrospinning procedures. PC12 cell viability and neurite outgrowth assays confirmed that the functionalized nanofibers were able to enhance axonal extensions. Significantly, compared to covalent immobilization and physical adsorption, blended electrospinning of laminin and synthetic polymer is a facile and efficient method to modify nanofibers for the fabrication of a biomimetic scaffold. Using these functionalization techniques, nanofibers can be effectively modified with laminin for potential use in peripheral nerve regeneration applications.